A new Neotropical genus of the family Cunaxidae (Acari: Prostigmata: Bdelloidea) - Den Heyer, Jacob; De Castro, Tatiane Marie Martins Gomes [UNESP] (My University, 2008)
A new Neotropical genus and its species, Allocunaxa heveae gen. et sp. nov., is described and figured. The generic features are provided. The subfamily Cunaxinae is discussed and a key to it is provided. Copyright © 2008.
Keywords: Bdelloidea; Cunaxinae; Identification key; Neotropical; Taxonomy